INTERPERSONAL COMMUNICATION STRATEGIES IN BUILDING AN IMAGE OF CONTIGENCY PERSPECTIVE OF ACCOMMODATION - Purwanto, Andrik; Wafa, Ali; Sanjani, M Aqil Fahmi (Universitas Nurul Jadid, 2023)
This research explores public relations strategies in educational institutions, focusing on the descriptive qualitative research method. Specifically, the study examines the public relations (PR) approach of Al-Manar Semboro Jember Islamic boarding school, which emphasizes interpersonal communication to cultivate a positive institutional image and foster trust within the community. Utilizing a humanistic approach, the school addresses community perceptions, assumptions, and needs promptly and effectively, prioritizing truth, speed, accuracy, friendliness, and comfort in its communication efforts. Key steps taken by the Islamic boarding school include home visits to engage with guardians, holding evaluation meetings, organizing religious activities and open days, and involving the community in school events, alongside providing a suggestion box for public feedback. These efforts underscore the school's commitment to enhancing staff communication skills, empathy, honesty, ethics, and emotional intelligence while prioritizing community needs and feedback. Through these initiatives, Al-Manar Semboro Jember Islamic Boarding School strives to maintain satisfactory relationships with stakeholders and deliver quality educational services.